EPISTEMOLOGI AL-FARABI DAN RELEVANSINYA BAGI PENGEMBANGAN FILSAFAT PENDIDIKAN ISLAM RASIONAL-RELIGIUS - Saraswati, Putri; Mukti, Abdul (Universitas Nahdlatul Ulama Surakarta, 2026)
Contemporary Islamic education faces the challenge of separation between rational-secular and religious-spiritual approaches, which hinders the formation of individuals who are intellectually and spiritually whole. This study aims to analyze Al-Farabi's epistemology as a philosophical foundation for the development of Islamic education that integrates rationality and religiosity. The research method uses a qualitative descriptive approach based on literature study with conceptual and hermeneutic analysis of Al-Farabi's works and related literature. The results show that Al-Farabi's epistemology, through the concept of the hierarchy of reason (potential, actual, acquired, and active reason) and the integration of reason and revelation, offers an educational framework that positions both as complementary elements in the process of acquiring knowledge, from sensory experience to the attainment of transcendental truth, with the ultimate goal of true happiness (al-sa'adah). The contribution of this research lies in strengthening the philosophical foundations of integrative Islamic education that transcends mere cognitive achievement to include character building and spiritual orientation, thus offering an alternative to modern educational models that separate knowledge from moral-spiritual values.